Incidence of Paradoxical Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome and Impact on Patient Outcome - Bonnet, Maryline (Public Library of Science, 2013)
OBJECTIVES AND DESIGN: We used data from a randomized trial of HIV-tuberculosis co-infected patients in Mozambique to determine the incidence and predictors of paradoxical tuberculosis-associated immune reconstitution inflammatory syndrome (IRIS) occurring within 12 weeks of starting antiretroviral therapy, and to evaluate its association with patient outcome at 48 weeks. METHODS: HIV-tuberculosis co-infected and antiretroviral therapy-naïve adults with less than 250 CD4/mm3 were randomized to a nevirapine or efavirenz-based antiretroviral therapy initiated 4 to 6 weeks after starting tuberculosis treatment, and were then followed for 48 weeks. Tuberculosis cases were diagnosed using WHO guidelines, and tuberculosis-IRIS by case definitions of the International Network for the Study of HIV-associated IRIS. RESULTS: The 573 HIV-tuberculosis co-infected patients who initiated antiretroviral therapy had a median CD4 count of 92 cells/mm(3) and HIV-1 RNA of 5.6 log(10) copies/mL. Mortality at week 48 was 6.1% (35/573). Fifty-three (9.2%) patients presented a tuberculosis-IRIS within 12 weeks of starting antiretroviral therapy. Being female and having a low CD4 count, high HIV-1 RNA load, low body mass index and smear-positive pulmonary tuberculosis were independently associated with tuberculosis-IRIS. After adjustment for baseline body mass index, CD4 count and hemoglobin, occurrence of tuberculosis-IRIS was independently associated with 48-week mortality (aOR 2.72 95%CI 1.14-6.54). Immunological and HIV-1 virological responses and tuberculosis treatment outcomes were not different between patients with and without tuberculosis-IRIS. CONCLUSION: In this large prospective cohort, tuberculosis-IRIS occurrence within 12 weeks of starting antiretroviral therapy was independently associated with the mortality of HIV-tuberculosis co-infected patients at 48 weeks post antiretroviral therapy initiation.